Pengaruh Exhaust Gas Recirculation (EGR) Terhadap Exhaust Gas Temperature (EGT) dan Smoke opacity Mesin Diesel 4JB1 Berbahan Bakar Biodiesel Jatropa-etanol - Syarifudin; Faqih Fatkhurrozak; Firman Lukman Sanjaya; Ahmad Farid (Infotekmesin, 2022)
Human dependence on motorized vehicles is getting higher and uncontrollable. This actualization will certainly have an impact on reducing fuel stocks and air pollution with soot emissions. Combining diesel fuel with jatropha and alcohol is predicted to reduce dependence on diesel fuel and air pollution. Supplying the combustion chamber with exhaust gas/Exhaust Gas Recirculation/EGR is also predicted to reduce soot emissions and reduce fuel consumption. This study aims to observe the effect of using the EGR system on the use of mixed fuel jatropha and ethanol exhaust gas temperature/EGT as an indication of performance and soot/smoke opacity as exhaust emissions. The experimental results show the use of the EGR system increases EGT and Smoke opacity decreases the diesel engine in each fuel variation. D100 fuel EGT increased 1.67%, DJ10 increased 0.71%, DJ10E increased 0.67%, DJ20 increased 1.45%, DJ20DE increased 1.07%, DJ30 increased 1.50%, and DJ30E fuel EGT increased by 1.47%. While on the emission side, the smoke opacity of D100 fuel decreased by 1.84%, DJ10 decreased by 1.71%, DJ10E decreased by 2.21%, DJ20 decreased by 0.96%, and DJ20E decreased by 2.33, DJ30 decreased by 2.99%, and DJ30E fuel decreased 1.30%.